Wujud Karakter Pelajar Pancasila dalam 66 Kisah Kebaikan untuk Anak - Citraningrum Dina Merdeka; Mohamad Afrizal; Rofiatul Hima (Universitas Muhammadiyah Jember, 2022)
This study describes the character form of Pancasila students in the text entitled